Optimal Continuous Review Policies for Two Product Inventory Systems with Joint Setup Costs - Ignall, Edward (Management Science, 1969)
Minimum average cost ordering policies for continuously reviewed two product inventory systems with joint setup costs are sought. Disappointly, the optimal policy, even in a simple symmetric case, is not always simple: For some values of cost and demand parameters, a policy that would be difficult to implement is optimal. Markov Renewal Programming is used to find the region in parameter space where a given policy is optimal.